Tendências temporais de mortalidade por câncer de próstata no estado do Espírito Santo - Gomes, Polyanna Fonseca Lobato Amorim (2014)
Prostate cancer is the second most frequent type of cancer in men in all regions of Brazil. Approximately 62 % of diagnosed cases worldwide occur in men aged 65 years or more, featuring the only established risk factor. Objectives: Study the trend of non-completion of the Mortality Information System (SIM), according to age, race / color, education and marital status in the period 2000-2010, in Espírito Santo, Brazil and Southeast region. Analyze trends in mortality from prostate cancer in the time series in the state of Espírito Santo (ES) in the period 1980-2010. Methods: We conducted a descriptive study based on secondary data of all deaths from prostate cancer and SIM data obtained from the Brazilian Institute of Geography and Statistics (IBGE) available on DATASUS, computer department of the SUS (Unified Health System) in ES, Southeast region and Brazil, in the period 1980-2010. Considered variables (age, race / color, education and marital status) and variable (age). We analyzed the absolute number and calculated the percentage of nonfulfillment of the information of DOs, which are the basis of information from the SIM, in selected locations (ES, Brazil and Southeast). Analyzed using the Statistical Package for Social Sciences (SPSS) version 18.0. Held an inferential analysis with curve adjustments to the percentages of missing demographic variables available in the Dataset (marital status, education, race / color) system data. And for trend analysis, calculating the mortality rate for deaths was performed. The equations of the model and the best fit statistics (R2 value and the p - value of F test of model fit) were obtained from SPSS, version 18.0. Results: In the period 2000 to 2010 the race / color variable, education, proved to be descending to Brazil. The education variable was found to be decreasing in Brazil, and the marital status variable, distinguished for characterizing a growing trend in ES, Brazil and Southeast. In the period 1980 to 2010 there was 3,561 deaths in the ES. Observed in the series history 's trend of mortality from prostate cancer. Conclusion: The study is of great importance for the study of prostate cancer in Brazil, we identified the increasing incompleteness of the fields of Civil Status. While the race - color variable was decreasing but with poor quality data. It takes actions so that the process of data collection is enhanced by training. Results show the trend of increased mortality, being necessary actions and strategies aimed at men completeness government policies.